17. YY ŞAİRLERİNDEN FEHİM, NA'İLİ VE NEŞATİ DİVANLARINDA KOZMİK UNSURLAR - YENTÜR, JULE (Fırat Üniveristesi, 2003)
Bu çalışma 17.yy Divân Edebiyatı şairlerinden Fehîm, Nâ'ilî ve Neşâtî divânları ndaki kozmik unsurların tespit ve tahlilini kapsamaktadır. Çalışmamıza Fehîm, Nâ'ilî ve Neşâtî'nin hayatı, sanatı, edebî kişiliği ve eserlerinin tanıtılması ile başlanılmıştır. Çalışmamızda kozmik unsurları üç şairin yorumlayış ve kullanış şeklindeki benzer ve orijinal kullanımları ortaya konulmuştur. Bu şairler, "Sebk-i Hindî " akımının temsilcisidirler. Bu nedenle de çalışmanın sonunda bu bağlamda kozmik unsurları nasıl algıladıkları ortaya konulmaya çalışılmıştır. Bu unsurların daha çok divânların kaside bölümünde yer aldığı ve şairler tarafından teşbih ve istiare unsuru olarak kullanıldığı tespit edilmiştir.

The scope of this study consists of determining and analysis of divan's cosmic elements from 17th century divân poems literature poets, Fehîm, Nâ'ilî and Neşâtî. It starts with the introduction of the life of Fehîm, Nâ'ilî, Neşâtî and their art, literary individuality, work of art. Similarities and originalities of the three poet's interpretations and usage of the cosmic elements have been studied. These poets are the representatives of the "Sebk-j Hindi" trend. For this reason at the end of this study, Poet's perception from the cosmic elements has been explained. These elements mostly stated at the eulogy part of divân and these elements has been used by the poets as simile and metaphor elements.
Cosmic elements in the divan poems of Fehim, Naili and Neaşati from 17th century
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature